Simultaneous balancing and trajectory tracking control for an omnidirectional mobile robot with a cylinder using switching between two robust controllers. (10th November 2017) - Alakshendra, Veer; Chiddarwar, Shital S
With the growing use of mobile robots in home applications, e-commerce warehouses, and so on it is necessary to pay attention to their object carrying capability for transferring objects from one location to another. The shape of the object to be carried may vary based on the type of surface (planar/nonplanar). For an instant, the surface of a cylinder is nonplanar. Thus, when the mobile robot tries to track a desired trajectory with a cylinder kept on its top surface, the cylinder may fall on the ground due to its uncontrolled rolling motion. Thus, in order to address the problem, this article presents a novel approach for a Mecanum wheeled mobile robot with a cylinder, for simultaneous balancing and tracking task. In this approach, first, the mathematical modeling of Mecanum wheeled mobile robot with the cylinder on its top surface is done using Newton–Euler approach. Then, to prevent the cylinder from falling, while Mecanum wheeled mobile robot is following a desired path, switching between two robust controllers is utilized to obtain a feasible reference trajectory. The robust control laws are derived using second-order sliding mode controller. In order to ensure the stability of the controller, Lyapunov stability proof of the established theorem has been provided. Later, the Mecanum wheeled mobile robot is made to follow a generated reference trajectory using the robust controller of the mobile robot. The proposed approach is implemented in MATLAB/Simulink. The simulation results proved the efficacy of the proposed approach such that Mecanum wheeled mobile robot followed the desired path with cylinder on its top surface. Moreover, results of statistical analysis have been presented, and comparison with proportional integral derivative (PID) controller is done to prove the superiority of the proposed approach.